AKIBAT HUKUM ITSBAT NIKAH DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN DAN HUKUM ISLAM - Siska Dwi Novitasari (Dinamika, 2020)
ABSTRACTIn the current era of globalization, there are still many Indonesian people, especially in rural areas whose level of education is still low and do not know more clearly the benefits of the itsbat marriage. Therefore, people need to understand how the implementation procedures and legal consequences of marriage law according to Law Number 1 of 1974 concerning Marriage and Islamic law. The method of study used is a normative research method that contains a description of what kind of research type of research, research approaches, types and sources of legal materials, techniques of obtaining legal materials, and legal material analysis techniques. So that it can be concluded the procedure of implementing itsbat marriage, namely making a request letter, registering an application letter to the registration counter to determine the SKUM court fee, the summons of the parties, the trial, and the reading of the decision. The legal consequence of the marriage is that marriage is considered legal by the State.Key words: itsbat marriage, religious courts, marriage, islamic law.ABSRAKDi era globalisasi zaman sekarang masih banyak masyarakat Indonesia khususnya di daerah-daerah Pedesaan yang tingkat pendidikannya masih rendah dan belum mengetahui lebih jelas manfaat-manfaat dari adanya itsbat nikah. Oleh karena itu, masyarakat perlu memahami bagaimana prosedur pelaksanaan dan akibat hukum dari itsbat nikah menurut Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan dan hukum Islam. Metode penelitian yang digunakan adalah metode penelitian normatif yang memuat uraian tentang jenis penelitian, pendekatan penelitian, jenis dan sumber bahan hukum, teknik memperoleh bahan hukum, dan teknik analisis bahan hukum. Sehingga dapat disimpulkan prosedur pelaksanaan itsbat nikah yaitu membuat surat permohonan, mendaftarkan surat permohonan ke loket pendaftaran agar ditentukan SKUM biaya panjar perkara, pemanggilan para pihak pemohon, persidangan, dan pembacaan putusan. Akibat hukum yang ditimbulkan dari itsbat nikah adalah perkawinan dianggap sah oleh Negara.Kata Kunci: Itsbat Nikah, Pengadilan Agama, perkawinan, hukum Islam.